APPLICATION OF THE SYNTHETIC ANALYTICAL STRUCTURAL METHOD TO IMPROVE THE READING SKILLS - Idris, Idris; Tahir, Moh.; Syamsuddin, Syamsuddin; Suputra, Gusti Ketut Alit; Nuraini, Nuraini; Hakim, Nur; Gazali, Gazali (Universitas Labuhanbatu, 2025)
Purpose – This study aims to evaluate the implementation of the Structural Analytic Synthetic (SAS) method in teaching beginning reading within the context of 21st-century skills, particularly during online learning environments prompted by the COVID-19 pandemic. It examines the extent to which first-grade teachers effectively apply the SAS method and align their instructional practices with the demands of modern literacy education.Methodology – This study employed a quantitative descriptive research design using a survey method. This research aims to analyze the extent to which teachers apply the Structural Analytic Synthetic (SAS) method in beginning reading instruction within the framework of 21st-century learning, particularly during the implementation of online learning in response to the COVID-19 pandemic. A total of 35 respondents were selected through a probability sampling technique, specifically using simple random sampling, and the sample size was determined based on the Krejcie and Morgan table at a 95% confidence level. The data collection techniques used in this study were questionnaires, structured interviews, and documentation.Findings – The findings of this study indicate that the implementation of the Structural Analytic Synthetic (SAS) method in teaching beginning reading during online learning has been generally successful, particularly in the context of 21st-century education. Teachers demonstrated a good level of mastery in applying the SAS method, as evidenced by consistent improvements in each observed session and positive responses from parents. The integration of 21st-century competencies—such as critical thinking, creativity, communication, and collaboration—was evident in teachers' instructional practices despite the challenges posed by the sudden transition to online learning during the COVID-19 pandemic.Contribution – This study contributes to improving early reading skills in first-grade students and offers a classroom strategy to enhance student reading comprehension outcomes.